Metode Pembelajaran Learning By Doing pada Pembelajaran Seni Musik : Studi Deskriptif pada Pembelajaran Seni Musik Kelas VI SLB-A Pembina Tingkat Nasional - Purwaningrum Rahayu; Marja Marja; Murni Winarsih (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
This study aims to obtain data on the music learning process using the Learning By Doing method with the melodica as a musical instrument for visually impaired sixth-grade students at SLB-A Pembina Tingkat Nasional (Special School for the Blind). Learning By Doing emphasizes the active involvement of students in the learning process. This is particularly relevant for visually impaired students, as they rely more heavily on their sense of hearing and touch to receive information. To gain a clear understanding of the stages of music learning using this method, the researcher employed a descriptive approach. Several data collection techniques were used, including interviews, observation of learning activities, document analysis, and field notes. The study was conducted over the course of one semester. The results of the research show that the implementation of the Learning By Doing method in music education involves three main stages: the planning stage (lesson plans and syllabus), the implementation stage (interactive learning and hands-on practice), and the evaluation stage. The application of Learning By Doing increased student engagement and understanding of basic musical tone concepts, and also supported their musical skills, auditory abilities, and experience in recognizing expression through sound. Thus, the Learning By Doing method is effective in teaching music to visually impaired students because it provides a concrete and meaningful learning experience.